ANALISIS EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENGENTASAN KEMISKINAN DI KAMPUNG NAWARIPI DISTRIK WANIA KABUPATEN MIMIKA - Fitri Aningsih Elia; Yahya Nusa (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2021)
This research was conducted in Nawaripi Village, Wania District, Mimika Regency.The purpose of this study was to study the effectiveness of the family hope program (PKH) in poverty alleviation efforts in Nawaripi Village, Wania District, Mimika Regency. The research method used is descriptive method. The data collection instrument used to obtain data in this study is to use interview list techniques, notebooks, and cameras. The results of this study show that: (1) Social services conduct socialization in accordance with Permensos No. 1 of 2018 on Family Hope Program; (2) Social services conduct socialization in accordance with Permensos No. 1 of 2018 concerning Family Hope Program; (3) The beneficiary of the Family of Hope Program (PKH) is a community that is able and worthy to meet the needs of its life; (4) PKH funds used by pkh recipients will not be used to improve the economy.